Pendekatan Seni Hibridisasi Dalam Penghasilan Karya Seni Area Instalasi - Mohd Syawal Fitri, Bin Jaludin (Universiti Malaysia Sarawak (UNIMAS), 2019)
This study is related to the approach of hybridization art in the production of installation artworks. The purpose ofthis study is to identify the elements and characteristics of hybrid art that can be utilized for the creation of installation sculpture artwork. The researcher employed a qualitative approach in the form of reference and observation in the process of data collection and conducting an analysis ofthe subject ofstudies. The outcome ofthe study is embodied in the form of artwork for final year projects. It is hoped that this research can be used as a reference to future researchers on the study towards a hybrid artwork.